INVESTIGATION OF THE INFLUENCE OF THE MANUFACTURING PROCESS ON THE STRUCTURE OF HYPEREUTECTIC ALUMINIUM-SILICON ALLOYS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Two technological approaches were used to produce the hypereutectic aluminium-silicon alloys AlSi21Cu5MgCr, AlSi21Cu5Cr, AlSi25Cu4Cr and AlSi25Cu5Cr. In one case, alloys were melted from pure metals, metallurgical processing of the melts was carried out, and experimental castings were cast. In the other case, remelting of previously prepared alloys was carried out for casting test castings from the studied alloys, and the metallurgical processing of the melts was carried out at a lower temperature. The influence of the method of obtaining the alloys on their structure has been established.